First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Remediation of water from perfluorooctanoic acid (PFOA) with ozonation and photocatalysis: Experimental studies and numerical modeling - Anastasios Melitsiotis; Konstantinos Christodoulis; Michalis Karavasilis; Nadia Bali; Maria Theodoropoulou; Masho Hilawie Belay; Davide Rotondo; Elisa Robotti; Emilio Marengo; Francesco Dondero; Christos D. Tsakiroglou (Process Safety and Environmental Protection, 2025)

The compensatory effect of education as revealed by resting-state electroencephalographic alpha rhythms in patients with dementia due to Parkinson’s disease: findings from an exploratory study - Susanna Lopez; Claudio Del Percio; Roberta Lizio; Giuseppe Noce; Dharmendra Jakhar; Andrea Soricelli; Marco Salvatore; Bahar Güntekin; Görsev Yener; Federico Massa; Dario Arnaldi; Francesco Famà; et al. (GeroScience, 2025)
Here, we investigated whether educational attainment influences the neurophysiological mechanisms underlying vigilance regulation, as reflected in resting-state eyes-closed electroencephalographic (rsEEG) rhythms, in patients with dementia due to Parkinson’s (PDD) and Lewy body disease (DLB). Clinical, demographic, and rsEEG data were obtained from an international database, including PDD patients ( N = 75), DLB patients ( N = 50), and cognitively unimpaired older controls (Healthy; N = 54). Each group was partitioned into low (Edu-) and high (Edu+) educational attainment subgroups, matched for age, sex, and cognitive-motor status. We analyzed rsEEG rhythms across the individual delta, theta, and alpha frequency bands. Cortical rsEEG source topography was estimated using eLORETA freeware. In the Healthy group, Edu+ participants exhibited significantly greater widespread rsEEG alpha source activities compared to Edu- participants, possibly reflecting neuroprotective neurophysiological mechanisms. Conversely, in the PDD group, Edu+ patients showed lower widespread rsEEG alpha source activities than Edu- patients, possibly indicating compensatory mechanisms. No significant differences in rsEEG source activities were observed between DLB-Edu+ and DLB-Edu- patients. Educational attainment may be associated with compensatory mechanisms that counteract the abnormal neurophysiological processes underlying rsEEG alpha rhythms and vigilance regulation in PDD patients, but not in DLB patients. Future studies combining rsEEG and neuroimaging techniques should investigate the metabolic and functional connectivity correlates of these putative compensatory mechanisms in the PDD brain. Early education may be a key investment for national governments, especially in low-income countries, to prevent the cognitive deficits of Parkinson’s disease along aging, thereby reducing the unbearable social and economic burden.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Evaluation of per- and polyfluoroalkyl substances (PFAS) toxic effects on the acute inflammatory response in the medicinal leech Hirudo verbana - A. Calisi; N. Baranzini; G. Marcolli; C. Bon; D. Rotondo; D. Gualandris; L. Pulze; A. Grimaldi; F. Dondero (Chemosphere, 2024)

P21-26: Neurotoxicity and biochemistry effect of Novel Perfluoroalkyl Ether Carboxylic Acids (PFECAs) in Earthworms (Eisenia foetida) - D. Rotondo; D. Gualandris; M. Manfredi; C. Lorusso; A. Calisi; F. Dondero (Toxicology Letters, 2023)

P13-17: Effect of Ether Perfluoro Carboxyl Acid (PFAS) on Innate Immunity in Earthworms - D. Gualandris; D. Rotondo; C. Lorusso; V. Audrito; A. Calisi; F. Dondero (Toxicology Letters, 2023)

Plasma microglial-derived extracellular vesicles are increased in frail patients with Mild Cognitive Impairment and exert a neurotoxic effect - C. Visconte; M.T. Golia; C. Fenoglio; M. Serpente; M. Gabrielli; M. Arcaro; F. Sorrentino; M. Busnelli; A. Arighi; G. Fumagalli; E. Rotondo; P. Rossi; et al. (GeroScience, 2023)
Extracellular vesicles (EVs) are mediators of cellular communication that can be released by almost all cell types in both physiological and pathological conditions and are present in most biological fluids. Such characteristics make them attractive in the research of biomarkers for age-related pathological conditions. Based on this, the aim of the present study was to examine the changes in EV concentration and size in the context of frailty, a geriatric syndrome associated with a progressive physical and cognitive decline. Specifically, total EVs and neural and microglial-derived EVs (NDVs and MDVs respectively) were investigated in plasma of frail and non-frail controls (CTRL), mild cognitive impairment (MCI) subjects, and in Alzheimer’s disease (AD) patients. Results provided evidence that AD patients displayed diminished NDV concentration (3.61 × 10 9 ± 1.92 × 10 9 vs 7.16 × 10 9 ± 4.3 × 10 9 particles/ml) and showed high diagnostic performance. They are able to discriminate between AD and CTRL with an area under the curve of 0.80, a sensitivity of 78.95% and a specificity of 85.7%, considering the cut-off of 5.27 × 10 9 particles/ml. Importantly, we also found that MDV concentration was increased in frail MCI patients compared to CTRL (5.89 × 10 9 ± 3.98 × 10 9 vs 3.16 × 10 9 ± 3.04 × 10 9 particles/ml, P < 0.05) and showed high neurotoxic effect on neurons. MDV concentration discriminate frail MCI vs non-frail CTRL (AUC = 0.76) with a sensitivity of 80% and a specificity of 70%, considering the cut-off of 2.69 × 10 9 particles/ml. Altogether, these results demonstrated an alteration in NDV and MDV release during cognitive decline, providing important insight into the role of EVs in frailty status.

High-resolution magic angle spinning nuclear magnetic resonance (HR-MAS-NMR) as quick and direct insight of almonds - Andrea Salvo; Archimede Rotondo; Valentina Mangano; Manuela Grimaldi; Ilaria Stillitano; Anna Maria D’Ursi; Giacomo Dugo; Luca Rastrelli (Natural Product Research, 2020)

Increased SAMHD1 transcript expression correlates with interferon-related genes in HIV-1-infected patients - Maura Statzu; Letizia Santinelli; Agnese Viscido; Claudia Pinacchio; Giancarlo Ceccarelli; Claudia Rotondo; Giuseppe Corano Scheri; Ivano Mezzaroma; Ombretta Turriziani; Guido Antonelli; Gabriella d’Ettorre; Carolina Scagnolari (Medical Microbiology and Immunology, 2019)

Characterization of phospholipid composition of pig plasma and erythrocyte membranes - G. Bruschetta; D. Alberghina; G. Nastasi; E. Rotondo; A. M. Ferlazzo (Veterinary Research Communications, 2008)

Cytokines and cytokine inducers stimulate prostaglandin E 2 entry into the brain - Davidson J.; Abul H.; Milton A.; Rotondo D. (Pflügers Archiv - European Journal of Physiology, 2001)